A FRAMEWORK FOR AN INDUSTRIAL ENGINEERING LEARNING FACILITY PARADIGM TOWARD INDUSTRY 4.0 - Sackey, Samuel Mensah; Bester, Andre; Adams, Dennit Quewan (The South African Journal of Industrial Engineering, 2020)
As the industrial world inches ever closer to adopting the Industry 4.0 paradigm, it becomes necessary to evolve a model industrial engineering (IE) learning facility framework that is comprehensive enough to accommodate the full range of exposures required to give students a total practical learning experience. This paper formulates a description model (morphology) and classification scheme for an IE learning facility that considers various levels of automation, including Industry 4.0, to support holistic IE education and training in South Africa. The literature is searched to investigate the state of the art in IE practical learning infrastructure. A questionnaire survey then determines the current status and practices among universities offering industrial engineering. This is followed by the construction of a learning facility framework embodying a mix of facility types, along with a delineation of their relevant characteristics, niches, and strengths that can be customised and deployed to maximise the practical experiences of students.